Complete sleep evaluation of top professional cross-country mountain bikers` athletes - Garbellotto, L.; Petit, E.; Brunet, E.; Gillet, V.; Bourdin, H.; Mougin, F. (The Journal of Sports Medicine and Physical Fitness, 2022)
BACKGROUND: Despite growing interest in athletes` sleep, few studies have focused on professional athletes, especially in individual sports. Moreover, limited investigations included female athletes. This study aimed to evaluate sleep chronotype, as well as objective and subjective sleep characteristics in male and female professional cross-country mountain bikers. METHODS: Thirteen athletes (7 males and 6 females) of the French national team took part in this study. The Chronotype was assessed by the Horne and Östberg Morningness-Eveningness Questionnaire and sleep by actigraphy for one month, by ambulatory polysomnography (PSG) for one night and by the Pittsburgh Sleep Quality Index. RESULTS: Most athletes (77%) are classified as moderately morning type and a minority of athletes (23%) are intermediate type. Athletes sleep on average 8 hours per night and during the night recorded by PSG, N3 and REM sleep stages represented 21.2±3.4% and 20.9±3.1% of the total sleep time, respectively. These good sleep parameters were confirmed by subjective data with 77% good sleepers. Except the poorer subjective sleep quality in female athletes (5.7±1.6) compared to male athletes (2.6±1.7, P<0.05), no significant sex difference was found for all characteristics evaluated. CONCLUSIONS: The professional status of these athletes and the organization of mountain bike calendar may explain their good sleep characteristics.